Identification of Potential Long Non-coding RNA Expression Quantitative Trait Methylations in Lung Adenocarcinoma and Lung Squamous Carcinoma - Wu, Xiaohong; Gao, Yue; Bu, Jianlong; Deng, Lin; Zhang, Pinyi; Chi, Meng; Jiang, Lihua; Shi, Xiaoding; Ning, Shangwei; Wang, Guonian (Frontiers in Genetics, 2020)
There are associations between DNA methylation and long non-coding RNA (lncRNA) which is also considered as lncRNA expression Quantitative Trait Methylations (lnc-eQTMs). lnc-eQTMs may perform a wide range of carcinogenesis. However, lnc-eQTM have not been globally identified and studied, and their roles in lung adenocarcinoma (LUAD) and lung squamous carcinoma (LUSC) are largely unknown. In present study, we identified some differential methylation sites (DMSs) located at long intergenic non-coding RNAs (lincRNAs) and other types of lncRNAs in LUAD and LUSC. An integrated pipeline was discovered to construct two global cancer-specific regulatory networks of lnc-eQTMs in LUAD and LUSC. The associations between eQTMs showed common and specific features between LUAD and LUSC. Some lnc-eQTMS were also related with survival in LUAD- and LUSC-specific regulatory networks. Lnc-eQTMs were associated with cancer-related functions such as lung epithelium development and vasculogenesis follow functional analysis. The drug repurposing revealed that these lnc-eQMTs maybe participate in some anaesthesia-related drugs in LUAD and LUSC. In summary, the present study elucidated the roles of lnc-eQTMs in LUAD and LUSC, which could be beneficial for understanding lung cancer pathogenesis and treatment.